Wereldse theologie: Publieke theologie en de economische wetenschap - Wijngaards, Aloys (Tijdschrift voor theologie, 2012)
This article searches for a way to connect public theology and economics as an academic discipline. Public theology is defined as the theological reflection on questions of meaning of life in the interactions and debates that people have on what they consider good, true, and beautiful, and what can be held as a shared and common good. There are several reasons for public theologians to focus their attention on economic matters. In studying the relation between economic behavior and questions of meaning of life, public theologians can benefit from the insights of economists. Yet, previous attempts at a conversation between theology and economics as an economic discipline have not been successful, as both methodological and epistemological issues hinder a connection between the two disciplines. In this article, two consecutive steps are taken to improve this situation. First, three relatively new approaches to economic theory that show an interest in evaluative deliberation and questions of meaning in economic behavior are explored: behavioral economics, happiness economics, and the capability approach. As these approaches appear to offer fertile ground for a conversation with public theology, it is worthwhile to elaborate the way in which the two disciplines can be connected. Therefore, in the second step, a framework is constructed that connects economic behavior to ultimate horizons of meaning. The framework is based on the value-theoretical work of the American pragmatist philosopher Nicholas Rescher. By arguing that evaluative arguments are a valid topic in a discussion between public theologians and economists (i.e. value objectivity) and by using cultivation hierarchies to connect concrete economic decisions to values and horizons of meaning, a framework that allows for a conversation between public theologians and economists can be envisioned. In this way, a ‘worldly’ theology can be constructed: a public theology that connects its theological analysis to insights from economics in order to study the relation between economic behavior and questions of meaning of life.